Pengaruh Dukungan Organisasi, Lingkungan Kerja dan Komunikasi terhadap Kinerja Pegawai pada Dinas Penanaman Modal dan Pelayanan Terdapadu Satu Pintu Muaro Jambi - Gilang Romadon; Sumarni Sumarni; Rohman Wilian (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research aims to determine the effect of organizational support, work environment, and communication on employee performance at the Investment and One-Stop Integrated Services Office (DPM-PTSP) of Muaro Jambi Regency, both partially and simultaneously. The method used is quantitative analysis with a population and sample consisting of all 44 employees, determined through a saturated sampling technique. Data were collected using a Likert scale-based questionnaire, and the analysis was carried out using multiple linear regression with the help of SPSS software. The results of the study showed that (1) organizational support has a positive and significant effect on employee performance, (2) work environment has a positive and significant effect on employee performance, (3) communication has a positive and significant effect on employee performance, and (4) organizational support, work environment, and communication simultaneously have a positive and significant effect on employee performance. The recommendations/suggestions from this research are expected to improve employee performance by enhancing organizational support through fair task distribution, reward programs, and development opportunities; creating a comfortable and well- equipped work environment that encourages productivity; and strengthening effective communication between superiors and subordinates as well as among employees through regular meetings and discussion forums.